Overexpression of miR-422a inhibits cell proliferation and invasion, and enhances chemosensitivity in osteosarcoma cells - Liu, Mingjiang; Xiusheng, He; Xiao, Xiangjun; Wang, Yichun (Oncology reports, 2016)
Osteosarcoma (OS) is an aggressive malignant tumor that is mesenchymal in origin with a very low 5-year survival rate, particularly in the patients with locally advanced or metastatic tumors and recurrent disease. MicroRNAs (miRNAs) play a critical role in essential biological processes as cellular proliferation, differentiation and apoptosis in normal or cancer cells, including OS cells. In the present study, we aimed to investigate the role of miR-422a in OS. We demonstrated that miR-422a expression was significantly downregulated in OS tissues and cell lines compared with the normal controls. In addition, overexpression of miR-422a was able to inhibit cell proliferation and the ability of invasion, and enhance paclitaxel and cisplatin-mediated apoptosis in OS cells. Inversely, downregulation of miR-422a exhibited an opposite role. We further demonstrated that miR-422a directly targeted TGFβ2 and regulated its expression and the activation of downstream molecules, smad2 and smad3 in OS cells. Thus, miR-422a/TGFβ2/smad axis may be a potential target for OS treatment.